PERLINDUNGAN ANAK TERHADAP KEKERASAN DALAM BERPACARAN (DATING VIOLENCE) DI KOTA BENGKULU - Zico Junius Fernando; M Abdi; Ria Anggraeni Utami; David Aprizon Putra (Universitas Bengkulu, 2021)
ABSTRACTIn Indonesia, the protection of children's rights is regulated in Law Number 23 of 2002 as amended by Law Number 35 of 2014 concerning Child Protection. Background of the issuance of Law Number 23 of 2002 as amended by Law Number 35 of 2014 concerning Child Protection for the Indonesian State to ensure the welfare of all its citizens, including protection of children's rights which are human rights as contained in the 1945 Constitution and the UN Convention on the Rights of the Child.Dating is a relationship between a man and a woman colored by intimacy where each other engages in feelings of love and acknowledges each other as partners. Whether we realize it or not, at this time many teenagers who are dating often commit bad behavior in dating relationships, one of which is violence in dating.Keywords: Children, Dating Violence.